Evaluation Parameter of Excessive Daytime Sleepiness for Obstructive Sleep Apnea Patients - Sang Hoo Park; Woo Yong Bae; Sangjun Kim; Young Gun Kim (Sleep Medicine Research, 2021)
Background and Objective Obstructive sleep apnea (OSA) is a sleep-related breathing disorder caused by repetitive obstruction of the upper airway. Repetitive obstruction of the upper airway causes impaired gaseous exchange, resulting hypoxia, hypercapnia, and frequent arousals of sleep architecture. Polysomnography (PSG) is a gold standard for diagnosing OSA. Excessive daytime sleepiness (EDS) is a common accompanying daytime symptoms in OSA patients. Since EDS can cause unexpected events such as traffic accident or poor performance in workplace, it is regarded as a significant public health problem. Therefore, accurate assessment and prediction of this symptom is important. The Epworth Sleepiness Scale (ESS) and multiple sleep latency test are most commonly used to evaluate EDS, but their efficacies are controversial. The purpose of this study is to find the parameter to evaluate and predict the EDS for OSA patients. Methods We retrospectively reviewed the medical records of 88 OSA patients. Patients were divided into two groups according to the presence of EDS. We analyzed the clinical records, questionnaire scores, and PSG data to find the difference between two groups. Results ESS was 10.64 ± 4.28 in EDS patients and 8.63 ± 4.86 in non-EDS patients. ESS showed a statistically significant difference between two groups (p = 0.044). Also, the percentage of 1st stage non-REM sleep in total sleep time (N1%) was 25.09 ± 15.24 in EDS patients and 18.97 ± 10.30 in non-EDS patients and showed a statistically significant difference between groups (p = 0.033). Patients’ weight was 81.59 ± 20.52 in EDS patients and 74.14 ± 12.63 in non-EDS patients and showed a statistically significant difference between groups (p = 0.046). Conclusions ESS, N1% and patients’ weight were significant parameter which is related with the presence of EDS for OSA patients. These parameters will be useful in evaluating the presence of EDS for OSA patients. Also, in patients diagnosed with sleep disorder with high N1%, EDS must be accurately evaluated as well.